Ubiór i tożsamość. O znaczeniu odzieży dla bohaterów transpłciowych - Kujawska-Kot, Anna (Instytut Socjologii Uniwersytetu Wrocławskiego, 2018)
The article takes up the issue of the importance of clothing for transgender people (focusing on transsexual people) during the transition process and after gender correction. The subject of the research are experience descriptions of transsexual women and men contained in egodocuments. The theory of Janet Verner Gunn’s autobiography, for whom the key categories are: life and synecdoche, was applied to the study of transsexual authors’ texts. The emotions expressed by the use of clothing allowing the externalization of the psychological gender were analyzed and interpreted. Attention was paid to the clothing worn every day, which informs how the heroes of autobiographical relations cope with looking in the social mirror: from the shyness expressed by androgynous clothing, through flashy outfit (resulting from the oppressive normalization), to finding a way to express themselves. The everyday wardrobe is an important element in the manifestation of identity consistent with the perceived sex for transsexual characters.
Keywords: outfit functions; gender identity; transsexual people; egodocuments; outfit palimpsestication